Historical Jesus research and systematic theology - Venter, Rian (Neotestamentica, 1995)
The alienation between New Testament scholarship and systematic theology concerning the historical Jesus is discussed. How the category 'historical Jesus' functions in systematic theologies is discussed and several emerging trends in christology are pointed out. The paper pleads for more meaningful interaction between New Testament scholarship and systematic christology. This may be achieved by (a) identifying the fundamental differences between systematic christology and the Third Quest, (b) searching for a common vision based on a common social location which reveals the inter-dependence of the two disciplines, and (c) accepting the critical challenges to historical Jesus research and to systematic theology.